2024
DOI: 10.1002/cssc.202301840
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the Full Potential of Infrared Spectroscopy for the Analysis of Technical Lignins

Ivan Sumerskii,
Stefan Böhmdorfer,
Otgontuul Tsetsgee
et al.

Abstract: We present an approach to overcome the challenges associated with the increasing demand of high‐throughput characterization of technical lignins, a key resource in the emerging bioeconomies. Our approach offers a resort from the lack of direct, simple, and low‐cost analytical techniques for lignin characterization by employing multivariate calibration models based on infrared (IR) spectroscopy to predict structural properties of lignins (i.e., functionality, molar mass). By leveraging a comprehensive database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
3
1
Order By: Relevance
“…Modeling of M w was found to provide more favorable RMSECV, R 2 CV, RMSEP, and relative error (RE) values than when predicting M n (Figure and Table ). This, as well as the relatively large bias in the regression line for the M n model, is in contrast to the observations by Sumerskii et al and as has been reported previously in our group for kraft lignin-based models. , The use of the logarithm of M w and M n was found to provide higher R 2 CV values and similar RMSECV/RMSEC (Table ), indicating that there is an improvement in the model’s reliability and no significant change in the degree of overfitting. The reduced RE in each case is due to linearization of the molecular weight values and thus the error, as has been reported by our group previously. , To our surprise, however, when changing from M n to log­( M n ), a decrease in R 2 Pred was found and observed, in spite of the similarly large increase in R 2 CV.…”
Section: Resultscontrasting
confidence: 58%
See 4 more Smart Citations
“…Modeling of M w was found to provide more favorable RMSECV, R 2 CV, RMSEP, and relative error (RE) values than when predicting M n (Figure and Table ). This, as well as the relatively large bias in the regression line for the M n model, is in contrast to the observations by Sumerskii et al and as has been reported previously in our group for kraft lignin-based models. , The use of the logarithm of M w and M n was found to provide higher R 2 CV values and similar RMSECV/RMSEC (Table ), indicating that there is an improvement in the model’s reliability and no significant change in the degree of overfitting. The reduced RE in each case is due to linearization of the molecular weight values and thus the error, as has been reported by our group previously. , To our surprise, however, when changing from M n to log­( M n ), a decrease in R 2 Pred was found and observed, in spite of the similarly large increase in R 2 CV.…”
Section: Resultscontrasting
confidence: 58%
“… 38 Very recently, Sumerskii et al followed up on this concept with a greatly expanded sample set (500+ lignins), with models correlating either mid-IR (MIR) or near-IR (NIR) spectra with lignin structural properties ( Figure 1 ). 40 Functional group contents could be well-predicted in this study. The M w range of the 500+ samples was vast, from 2170 to 38 9500 g mol –1 for the lignosulfonates, and from 1190 to 70 900 g mol –1 for the kraft lignin samples.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations